KONDISI LINGKUNGAN DALAM PEMELIHARAAN LARVA CACING NIPAH Namalycastis rhodochorde DI LABORATORIUM - Edo, Febry Valianto; Junardi, Junardi; Yanti, Ari Hepi (Jurnal Protobiont, 2020)
The cultivation of Namalycastis rhodochorde nypa worms is still experiencing obstacles due to the high mortality rate of larvae, which can be caused by unsuitable conditions for the maintenance media. This study aims to obtain data on the conditions of environmental factors during larval rearing in the laboratory. This study observed environmental factors in 5 larval rearing treatments, namely 50, 100, 150, 200, 250 individuals/L with the size of the rearing tub (37×26×14 cm3). During rearing larvae are given 0.3×10-3 Chlorella vulgaris feed and fermented palm fronds. Data were collected every 10 days for 3 months. The parameters for observing environmental factors were water pH, water temperature, air temperature and salinity.  The results showed that the average water pH was 7.6 with a range between 7.3-7.9, an average water temperature of 25.6 °C with a range between 24-28 °C, an average air temperature of 25.9 °C with a range between 24-29 °C, and the mean salinity of 13.7 ppt with a range between 13-16 ppt. The results of the research on water quality during maintenance were relatively standard, thus supporting survival and growth of N. rhodochorde nipah worms.